Purified dispersions of graphene in a nonpolar solvent via solvothermal reduction of graphene oxide1. Issue 18 (4th March 2015) - Zheng, Fei; Xu, Wei-Long; Jin, Han-Dong; Zhu, Meng-Qi; Yuan, Wei-Hao; Hao, Xiao-Tao; Ghiggino, Kenneth P.
<x xml:space="preserve">Abstract</x> It is demonstrated that oxidative debris can be separated and largely removed during the surfactant assisted phase transfer of graphene oxide from a water/ethanol mixture to dichlorobenzene.